MATRIKS HANKEL - Tjahjana, R. Heru (MATEMATIKA, 2001)
In  this paper,  we talk  about Hankel  Operator and  Hankel Matrix. Operator Hg:F[z]®z-1F[[z-1]] defined by  Hg(f)=p_(gf) is called the Hankel Operator. Hankel Operator can be represented by a Hankel matrix.